Teaching work in the capital of the globalization era: analysis of its productive condition and immaterial - Roncato, Rodrigo (Revista Hipótese, 2015)
This article presents a literature review related to the discussion teaching. From the socio-historical and political understanding of the facts produced a series of transformations in the last three decades, it highlights the concerns that come to restructure the capital accumulation mode. The goal was to understand how characterized the teaching today, analyzing how has become more alienated and taken as an important action to maintain the dominant interests.
Keywords: Teaching; Knowledge; Productive restructuring; Immaterial